ASSESSING THE COGNITIVE IMPACT OF DIGITAL EDUCATION IN EARLY CHILDHOOD (NEP 2020) - Aman, Raj (International Journal of Research -GRANTHAALAYAH, 2025)
The nature of education has changed today. In the new education policy, work is being done to improve the quality of this education, increase education, and make the experience of students more attractive. ICT is the beginning of innovation in traditional teaching for children. Today, scientificity is being used in ECI with the aim of practicing new methods in the education of young children, teaching them in new ways, promoting their practice, social and academic development. For this, the use of statistics is more important in the quality of education today. It is not only to achieve the learning ability of children, but it is also important to make the learning ability more effective in teaching. Through this, the learning experience becomes more personal, active, and temporary. Advanced teaching tools for children such as smart classrooms, projectors, and interactive whiteboards are able to create more engaging and easy to understand tools for children. To improve the quality of education by ICT, Dynesis, interactive games, audio-visual materials, and other digital classrooms are being used to make learning more effective in the classroom. Both the government and the private sector are promoting the extensive use of science to ensure quality early childhood education for all children. Both the government and the private sector are promoting the extensive use of science to ensure quality early childhood education for all children. There are a good number of early kindergarten and private service providers in India like nursery school, kindergarten, play school school in Patna. It is constantly increasing (private service provider). In Bihar, it is not yet fully operational in a transformative form. This is the time when it is necessary for service providers to know how ICT is being used in ECCE to make education more effective, convenient and inclusive and what problems can be faced among these students.The present research was conducted with the lowest students in this context.